Rise and Decline of the Roman Civilization - Sultana, Zakia (Mediterranean Journal of Social Sciences, 2012)
Rome expanded across the Mediterranean and grew into a huge, diverse empire. By the end of the fourth century B.C.E.Rome was already the dominant power on the Italian Peninsula. For five centuries thereafter Romeâ€™s power steadily increased. Romeâ€™sdestruction of the powerful North African City of Carthage united the entire Mediterranean world and made the Mediterranean itself aâ€œRoman Lakeâ€. Rome began as a small city state in Italy. The Romans were an Indo-European people who settled along the Tiber Riverin small villages. Their neighbors, the Etruscans, ruled much of central Italy, including Rome. After the Romans threw out the hatedEtruscan king in 509 B.C., they resolved never to be ruled by a monarch again. Instead they set up a republic, a government in whichofficials are chosen by the people. At first, the most powerful people in government were Patricians, or members of the landholdingupper class. Eventually, commoners, or Plebeians were also elected to the Roman Senate. Military victories put the Romans in control ofbusy trade routes. Incredible riches flooded into Rome faced and this causes a series of civil wars. Eventually, a powerful Romangeneral named Augustus restored order. Under Augustus, who ruled from 31 B.C to A.D.14, the 500 year old republic came to an end. Anew age dawned â€“ the age of the Roman Empire. Augustus laid the foundation for a stable government and undertook economicreforms. The 200 years span that began with Augustus ended with emperor Marcus Aurelius. It is Known as the Pax Romana, orâ€œRoman Peaceâ€. During the time, Roman emperors brought peace, order, unity and prosperity to the lands under their control. Romeacted as a bridge between the east and the west by borrowing and transforming Greek and Hellenistic achievements to produce Greco-Roman Civilization. The Romans greatly admired Greek culture. They took Greek ideas and adapted them in their own ways. Romansculptors, for instance, used the Greek idea of realism to reveal an individualâ€™s character in each stone portrait. Probably the greatestlegacy of Rome was its commitment to the rule of law and to justice. These shape western civilization today. After the death of theemperor Marcus Aurelius in A.D.180, turmoil rocked the Roman Empire split into two parts, east and west, each with its own ruler in thewest. The foreign invaders marched into Italy and, in 476, took over Rome itself. But the Roman Empire did not disappear from the map.The eastern Roman Empire prospered under the emperor Constantine. In time, the eastern Roman Empire became known asByzantium. It lasted for another 1,000 years. The article discussed on overall Roman Civilization â€“ the rise and fall of Roman Empire withits political changes and the prosperity of Romans during their rule.